2006
DOI: 10.1051/0004-6361:20053593
|View full text |Cite
|
Sign up to set email alerts
|

The ratio ofN(C$\mathsf{^{18}}$O) andA$\mathsf{_{V}}$ in Chamaeleon I and III-B

Abstract: The shallow proportionality suggests that C 18 O is heavily depleted in these regions. As the degree of depletion is proportional to the gas density, these regions probably contain very dense, cold cores, which do not stand out in CO mappings. A comparison with the dust temperature map derived from the ISO data shows that the most prominent of the potentially depleted cores indeed coincides with a dust temperature minimum. It seems therefore feasible to use N(C 18 O) and A V data together for identifying cold,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 57 publications
8
37
0
Order By: Relevance
“…6 and the online material for a color version. We note that our extinction value is in between the A V of 7.9 mag measured in a slope in the A V map from Kainulainen et al (2006) and the first ever measured value of 3.55 mag by Neuhäuser & Comerón (1998). Given the quality of our fit, we find here further evidence for the physical binarity of Cha Hα 2 being a double of almost identical mid-to late-M-type objects.…”
Section: Spectroscopysupporting
confidence: 74%
“…6 and the online material for a color version. We note that our extinction value is in between the A V of 7.9 mag measured in a slope in the A V map from Kainulainen et al (2006) and the first ever measured value of 3.55 mag by Neuhäuser & Comerón (1998). Given the quality of our fit, we find here further evidence for the physical binarity of Cha Hα 2 being a double of almost identical mid-to late-M-type objects.…”
Section: Spectroscopysupporting
confidence: 74%
“…Our map looks very similar to the extinction map of Kainulainen et al (2006) in terms of structure and sensitivity. Their map was also based on 2MASS data and a similar method was used to compute the extinction.…”
Section: Extinction Map From 2masssupporting
confidence: 71%
“…In their study of the Chamaeleon complex, Hayakawa et al (2001) found evidence of variations of 13 CO versus A V from cloud to cloud, which they attributed to chemical fractionation increasing the 13 CO abundance in regions with 2 mag < A V < 4 mag. Although their result was not confirmed by Kainulainen et al (2006), CO abundance variations may exist and may complicate the statistical analysis of CO maps. As Padoan et al (2004) assumed a constant 13 CO abundance in their models, it is possible that the 13 CO power spectra that they derive are affected by variations in the 13 CO abundance.…”
Section: Discussionmentioning
confidence: 92%